2022
DOI: 10.7554/elife.77014
|View full text |Cite
|
Sign up to set email alerts
|

Mettl3-mediated m6A modification of Fgf16 restricts cardiomyocyte proliferation during heart regeneration

Abstract: Cardiovascular disease is the leading cause of death worldwide due to the inability of adult heart to regenerate after injury. N6-methyladenosine (m6A) methylation catalyzed by the enzyme methyltransferase-like 3 (Mettl3) plays an important role in various physiological and pathological bioprocesses. However, the role of m6A in heart regeneration remains largely unclear. To study m6A function in heart regeneration, we modulated Mettl3 expression in vitro and in vivo. Knockdown of Mettl3 significantly increased… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Contrary to Kun Zhao et al, studies have shown that transfection of small interfering RNA targeting METTL3 can promote CMs proliferation, while overexpression of METTL3 has the opposite effect . Moreover, METTL3 overexpression decreased cardiomyocyte proliferation and suppressed heart regeneration in postnatal mice . The above-mentioned studies highlight the different roles of METTL3 in different pathological processes and at different time points.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Contrary to Kun Zhao et al, studies have shown that transfection of small interfering RNA targeting METTL3 can promote CMs proliferation, while overexpression of METTL3 has the opposite effect . Moreover, METTL3 overexpression decreased cardiomyocyte proliferation and suppressed heart regeneration in postnatal mice . The above-mentioned studies highlight the different roles of METTL3 in different pathological processes and at different time points.…”
Section: Resultsmentioning
confidence: 85%
“…35 Moreover, METTL3 overexpression decreased cardiomyocyte proliferation and suppressed heart regeneration in postnatal mice. 36 The above-mentioned studies highlight the different roles of METTL3 in different pathological processes and at different time points.…”
Section: Characterization Of Dpdmnsmentioning
confidence: 99%
“…Gong et al showed that loss of METTL3 promoted cardiomyocytes cell cycle re-entered, infract size decreased and cardiac function improved after myocardial infarction by reducing primary miR-143 m 6 A modification [ 28 ]. Similarly, Jiang et al revealed that Mettl3 deficiency obviously increased cardiomyocyte proliferation and facilitated heart regeneration following heart injury in neonatal and adult mice [ 29 ]. On the contrary, Zhao et al .…”
Section: Discussionmentioning
confidence: 99%
“…METTL3 is a pivotal catalytic subunit in the methyltransferase complex. Its expression increases in the postnatal mouse heart and following neonatal heart injury but does not change after MI-induced injury in the adult heart [50]. The overexpression of METTL3 suppresses the proliferation of primary CMs isolated from neonatal mice and inhibits cardiac regeneration in vivo, whereas the knockdown of METTL3 increases CM proliferation and promotes cardiac regeneration after MI-induced heart injury in neonatal, postnatal, and adult mice [50,51].…”
Section: Ythdf2 Mediates the Activity Of Mettl3 To Prevent Excessive ...mentioning
confidence: 99%